2022
DOI: 10.1016/j.celrep.2021.110213
|View full text |Cite
|
Sign up to set email alerts
|

Seipin localizes at endoplasmic-reticulum-mitochondria contact sites to control mitochondrial calcium import and metabolism in adipocytes

Abstract: Highlights d Seipin is enriched at ER-MAMs d Seipin interacts with MAM calcium regulators in a nutritionally regulated manner d Adipocyte seipin deficiency impairs mitochondrial calcium import and ATP production d Inducible seipin removal from adipose tissue leads to rapid mitochondrial dysfunction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 70 publications
2
50
0
Order By: Relevance
“…Food intake was not increased. Finally, tamoxifen-inducible seipin deletion under the ERT2-AdipoQ promoter also induces a progressive loss of adipose tissue, strongly supporting that seipin is required for mature adipocyte maintenance [ 45 , 46 ].…”
Section: Seipin Deficiency Leads To Severe Lipodystrophymentioning
confidence: 99%
See 4 more Smart Citations
“…Food intake was not increased. Finally, tamoxifen-inducible seipin deletion under the ERT2-AdipoQ promoter also induces a progressive loss of adipose tissue, strongly supporting that seipin is required for mature adipocyte maintenance [ 45 , 46 ].…”
Section: Seipin Deficiency Leads To Severe Lipodystrophymentioning
confidence: 99%
“…Together with the increased NEFA release, several studies reported an increase in FA oxidation and thermogenesis [ 45 , 56 ] in seipin-deficient WAT. Recently, using an inducible deletion of seipin, we reported that this induction of FA catabolism was transitory, suggesting that it may be an early event accounting for the loss of TAG store in seipin-deficient adipose tissue [ 46 ]. Altogether, several pieces of evidence support that abnormally elevated NEFA release and catabolism might contribute to the lipodystrophic phenotype of seipin-deficient mice.…”
Section: Seipin Deficiency Leads To Severe Lipodystrophymentioning
confidence: 99%
See 3 more Smart Citations